Team UMP emerged as winner in Malay Category in Royal Debate - Mohd Ferdaus, Musa
Universiti Malaysia Pahang (UMP) debate team did the university proud when they emerged as champion in the Malay category in the Royal Debate 2012 by beating Universiti Kebangsaan Malaysia (UKM) team at the finals held at Cultural Hall, USM, Penang on February 15, 2012.